A study on 6-year-old preschoolers' musical skills and their parents' rhythmic skills - (:unkn) unknown (ELSEVIER SCIENCE BV, 2009)
Rhythm education, a method used in pre-school music education, forms the basis of children's musical skills. Thus, children with sound rhythm education grasp the other basic elements of music more easily and learn music faster. Rhythm education is thus an important aim of music education. In this survey, the descriptive method has been used with the purpose of determining the relation between the musical skills of 6-year-old preschoolers and the rhythmic performance of their parents. The participating children were chosen among students at independent preschools affiliated with the Ministry of Education and located in the Asian side of Istanbul. The results showed that the rhythmic skills of 6-year-old children varied in favour of boys and that there was a positive correlation between the rhythmic skills of 6-year-old children with that of their parents and between the rhythmic skills of children with other musical skills. In addition, it was revealed that the rhythmic skills of children whose parents were working were higher than the rhythmic skills of children whose parents were not working.
Keywords: Musical skills; rhythm; rhythmic skill; pre-school education